An integrated hospital-to-home transitional care intervention for older adults with stroke and multimorbidity: A feasibility study. (20th April 2020) - Markle-Reid, Maureen; Valaitis, Ruta; Bartholomew, Amy; Fisher, Kathryn; Fleck, Rebecca; Ploeg, Jenny; Salerno, Jennifer
Background: Stroke is the leading cause of death and adult disability in Canada. Eighty percent of older adults (≥65 years) who have suffered a stroke will return to their homes, and 60% will require ongoing rehabilitation. The transition between hospital and home is often fragmented, leading to adverse health outcomes, hospital readmissions, and increased health-care costs. This study examined the feasibility of a 6-month integrated transitional care stroke intervention (TCSI), and explored its effects on health outcomes, patient and provider experience, and cost in 30 community-living older adults (≥55 years) with stroke and multimorbidity (≥2 chronic conditions) using outpatient stroke rehabilitation services. Methods: The TCSI is a 6-month intervention delivered by an interprofessional (IP) team (occupational therapist, physiotherapist, speech language pathologist, registered nurse, social worker). It involved care coordination, home visiting, and IP case conferences, supported by a web-based application. A qualitative descriptive approach was used to explore the feasibility of implementing the intervention. A prospective one-group pretest/posttest was used to evaluate the effects of the intervention on health outcomes and use and costs of health services, from baseline to 6 months. Results: Participants had an average of eight comorbid conditions. The intervention was feasible and acceptable to both older adults and providers. From baseline to 6 months, there was no statistically significant difference in health outcomes. However, there was a significant reduction in the total per person use and costs of health services. Conclusions: This study established the feasibility of conducting a larger randomized controlled trial of this intervention.